2013
DOI: 10.1016/j.bbamcr.2012.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Calcium sensing receptor signalling in physiology and cancer

Abstract: The calcium sensing receptor (CaSR) is a class C G-protein-coupled receptor that is crucial for the feedback regulation of extracellular free ionised calcium homeostasis. While extracellular calcium (Ca(2+)o) is considered the primary physiological ligand, the CaSR is activated physiologically by a plethora of molecules including polyamines and l-amino acids. Activation of the CaSR by different ligands has the ability to stabilise unique conformations of the receptor, which may lead to preferential coupling of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
128
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 128 publications
(135 citation statements)
references
References 162 publications
5
128
0
2
Order By: Relevance
“…This finding was in agreement with another study, which also showed that cation-sensing receptors are not activated by Zn 2+ (Riccardi 1999). The other well-described cation receptor is the Ca 2+ -sensing receptor (CaSR) (Brown 2000;Brennan et al 2013); despite the link between these ions, the Zn 2+ -dependent Ca 2+ increase was distinct from the activity of the CaSR as overexpression of CaSR did not produce an increase in Ca 2+ following application of extracellular Zn 2+ (Hershfinkel et al 2001 2+ , enhanced activation of the mitogen-activated protein (MAP) kinase pathway and the PI3 kinase pathways was observed. These pathways are closely linked to enhanced cell survival and proliferation (Chappell et al 2011), and thus the ZnR may be the mediator of the well-established role of Zn 2+ (MacDonald 2000).…”
supporting
confidence: 89%
“…This finding was in agreement with another study, which also showed that cation-sensing receptors are not activated by Zn 2+ (Riccardi 1999). The other well-described cation receptor is the Ca 2+ -sensing receptor (CaSR) (Brown 2000;Brennan et al 2013); despite the link between these ions, the Zn 2+ -dependent Ca 2+ increase was distinct from the activity of the CaSR as overexpression of CaSR did not produce an increase in Ca 2+ following application of extracellular Zn 2+ (Hershfinkel et al 2001 2+ , enhanced activation of the mitogen-activated protein (MAP) kinase pathway and the PI3 kinase pathways was observed. These pathways are closely linked to enhanced cell survival and proliferation (Chappell et al 2011), and thus the ZnR may be the mediator of the well-established role of Zn 2+ (MacDonald 2000).…”
supporting
confidence: 89%
“…Blocking/inhibiting Trpv5/6 activity using four TRPV5/6 inhibitors/blockers all resulted in elevated pAkt signal in NaR cells under normal [Ca 2 þ ] conditions. These data suggest that Trpv5/6 represses IGF signaling and suppresses NaR cell proliferation under normal 27 Activation of CaSR has been shown to increase mammalian TRPV5 activity. 38 This possibility was not supported by our data.…”
Section: Discussionmentioning
confidence: 71%
“…The Ca 2 þ -sensing receptor (CaSR), a class C G-protein-coupled receptor that senses and is activated by high extracellular [Ca 2 þ ], has a key role in maintaining Ca 2 þ homeostasis by regulating the release of parathyroid hormone (PTH). 27 The CaSR is expressed in the entire digestive tract, including the colon, and has been hypothesized to be a major driver of colon cell differentiation under high extracellular [Ca 2 þ ]. 28 However, addition of NPS 2143, a selective CaSR antagonist, 29 to cultured Caco-2 cells did not affect IGF-induced Akt signaling in either normal or low [Ca 2 þ ] conditions (Figure 8e).…”
Section: Resultsmentioning
confidence: 99%
“…Asimismo, la suplementación con Ca reduce la recurrencia de los adenomas de colon. Según diversos estudios, este efecto del Ca se relaciona con la capacidad de este catión de unirse a ácidos grasos y ácidos biliares en la luz intestinal, evitando que ambos, en su forma ionizada, puedan ejercer un efecto proliferativo sobre los colonocitos, aumentando la probabilidad de formación de células con errores del genoma (20).…”
Section: Calcio Y Cáncerunclassified